KAJIAN ILMIAH: KARAKTERISTIK UBI KAYU HASIL PEMULIAAN SEBAGAI SUMBER PANGAN MASA DEPAN - Rina Heldiyanti (The Journal of Teknologi Pangan, 2023)
It is necessary to increase cassava production because cassava is a pillar in the food diversification program to support national food security. The demand of cassava is increasing because it is widely use not only in food industry but also in feed, energy and pharmacy industry. Thus, a policy is needed where cassava research is directed at the formation and utilization of early-mature, high-yielding, high-starch cultivars. The important characteristics of cassava that need to be developed as a food ingredient are high productivity, high starch content and low cyanide acid (HCN) content. In order to get the desired character, breeding program with high plant genetic diversity requirements need to be carried out through mutation induction using Gamma irradiation. The use of gamma light will increase the characteristic diversity due to its ability to change gen structure, chromosome structure and amount of chromosome. This literature study differs on the potential of cassava from breeding with different varieties as a potential food source in the future based on its characteristics. The aim of this review was to give an ideal information from various researchs regarding the development and potential of mutant cassava. Based on previous researchs, it can be seen that each variety of mutant cassava shows different characteristics and also different utilization.